Dialectics and the Relationship between Philosophy and Religion in an Islamic Perspective - Muhammad Adip Fanani (MAQOLAT: Journal of Islamic Studies, 2024)
.  Islamic philosophy and religion have undergone long phases of ups and downs, becoming a dialectic of science. Religion and philosophy in the academic world view are two entities that cannot be separated when studied academically to find the truth. Ibn Rushd asserted that the religion of sharia and the philosophy of wisdom do not conflict. Indeed, there was tension between theologians, especially al-Ghazâlî in Tahâfut al-Falasifah, and Islamic philosophers, especially peripatetic philosophers, such as Ibn Sina. This tension is reflected in Ibn Rushd's statement that "reproach from friends hurts more than reproach from enemies, because according to him, religion and philosophy are actually brothers." The research in this article uses descriptive qualitative research methods with a Library Research approach, visualizing and analyzing the phenomena in this research study. The data sources in this research come from various information, journals, and writings resulting from research on the dialectics of Islamic philosophy and religion. The focus of discussion in this article has three focuses of discussion starting from measuring the relationship between Islamic philosophy and religion, characteristics of philosophy and religion in Islam, and dialectics of philosophy and Islamic religious teachings. Philosophy and religion are two entities that cannot be separated and will continue to be discussed and studied because they are academic studies, in search of scientific and rational truth.